Patterns of Conjunctive Relation (CR) in Phases and Stages of Narratives in Year Three Junior High School English Books and Their Pedagogical Implication - Agus Dwi Priyanto; Tri Wiratno; Yanuar Yanuar; Djatmika Djatmika; Riyadi Santosa (Teacher Training and Education Faculty, Widya Gama Mahakam Samarinda University, 2022)
Background: This study is intended to find out the patterns of CR used in developing phases and stages of narrative and their implication in the genre-based model of language teaching of narratives. The study uses 15 different narratives from two nationally recognized Junior High School English books published by Intan Pariwara and Tiga Serangkai as data sources. Methodology: The narratives are analysed based on their functional engagements of phases and rhetorical functions of stages. Then, the patterns of CR in each phase and stage of the narratives are identified in terms of their types, meanings and roles to develop the phases and stages of narratives. Findings: The findings indicate that the logic of space of external addition and internal similar comparison are used in describing Character, Setting, and Activity in Orientation. Meanwhile, the combination of logic of space and time of external different comparison, external successive time and cause consequence are mainly used to develop phases of Introducing Problem, Developing Problems to Climax in Complication, Evaluation, and phases of Effort 1 to N, Problem Solved in Resolution. Coda, finally, applies internal similar comparison and external successive time to make comments and extract the value of the story. Conclusion: The intricate patterns of CR used in different phases and stages of narrative should be taught delicately in guided and scaffolded instructions through four stages of genre-based model of teaching, namely, BKOF, Modelling, JCT and ICT. Originality: This area of research is under widespread scrutiny and investigation especially conjunctive relationship in each step and phase, as well as the instructional implications of narrative texts.